7a+4b-3a-5b=

Simple and best practice solution for 7a+4b-3a-5b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7a+4b-3a-5b= equation:


Simplifying
7a + 4b + -3a + -5b = 0

Reorder the terms:
7a + -3a + 4b + -5b = 0

Combine like terms: 7a + -3a = 4a
4a + 4b + -5b = 0

Combine like terms: 4b + -5b = -1b
4a + -1b = 0

Solving
4a + -1b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add 'b' to each side of the equation.
4a + -1b + b = 0 + b

Combine like terms: -1b + b = 0
4a + 0 = 0 + b
4a = 0 + b
Remove the zero:
4a = b

Divide each side by '4'.
a = 0.25b

Simplifying
a = 0.25b

See similar equations:

| -12+4m=2m+2 | | 6z=4z+12 | | 6z=4z+12 | | 11+4=-5(6x-3) | | -7z+12z^2-12=0 | | 4(x+3)-(6n+6)= | | 39+4y-16=17y-13-4y | | 6(x+4)-9=2x+4(5+x) | | y-5=-5(x+6) | | 20x-16=20x+7 | | 4(x+12)-(6n+6)= | | 2x+7y=k+8 | | 3y^2+65=2y^2+127 | | 20x-16=20x+4 | | 0.85x+0.05(10-x)=0.10(-27) | | -7(3x-3)+6=-21x+27 | | 3x^2+3y^2+15y+9x+12=0 | | 2x(3x-9)-4=2(x-3) | | 6(18.5)-3=x | | 11r^2+28=0 | | -7(3x-3)+6=-21x+7 | | (5+x^4)-(3x^4+4x)=0 | | h(x)=x^2+9x+8 | | 2(-3y-1)+(2y+7)=a | | 2x+5+6x-3+30=180 | | 40.7=5b | | -3(x+9)+6x=-6 | | 3(x^3+2x^2+8x+36)=0 | | -9d-8=154 | | -0.10(13)+0.20x=0.05(x-14) | | 5(3x-6)-4=5(x-4)+76 | | 8n^2=24n+320 |

Equations solver categories